CULTURAL LANDSCAPE AS OUTSTANDING UNIVERSAL VALUE: SAWAHLUNTO CASE STUDY - Amanda Rosetia; Rika Cheris (Journal of Architectural Design and Development (JAD), 2023)
Cultural landscape not only suggesting the agents that evolve within them, but also the transport of ubiquitous entity that changing around the agents themselves. More than that, cultural landscape has a core capability to revoke an abandoned story of an area. Sawahlunto city with its definite historical evolution as an mining city, has been nominated as an UNESCO World Heritage List in 2019. Notwithstanding, its criterion are listed as a property that seen to be tangible element. The value of this historic district are more than just rustic steel and concrete. The aim of this paper is to extend the explanation that cultural landscape element of Sawahlunto city has the capability to be carried as an outstanding universal value. Using UNESCO 2011 key element on defining OUV criteria, this paper will discuss the purport and concept of cultural landscape values of the city. A review of antecedents of cultural landscape definition will also be made. Through this, a discussion will be provoked to bring out more thoughts on considering intangible element into a heritage area development as one of the sustainable approaches for tourism destination.